Identifikasi Soal-Soal Hots pada Buku Ajar PAI Kelas 12 SMA Negeri 1 Ciomas - Citra Ilmiah Awaliah; Edisti Aditia; Jakiatun Nupus; Saefudin Dzuhri; Wahyu Hidayat (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This research used the revised version of Bloom's Tax theory analysis to examine the Islamic Religious Education (PAI) question quality for grade XII at SMA Negeri 1 Ciomas. Data for this study comes from a variety of sources, including interviews with PAI instructors, recordings of final exam questions, and literature reviews and library research. The research methodology is qualitative descriptive, and the question bank is based on Islamic religious education. Remembering, comprehending, applying, analyzing, evaluating, and producing are the cognitive categories that are the center of attention in the updated Bloom's Taxonomy. The study's findings show that low-level cognitive abilities, such as remembering and comprehending, account for the vast majority of PAI questions, whereas higher-level cognitive abilities, such as analyzing and inventing, are shown by a far lower fraction. This shows the need for better question preparation in order to enhance students' HTS. The hope is that these results will help improve PAI curricula and pedagogical approaches.